2018
DOI: 10.1186/s12887-018-1242-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and child patterns of Medicaid retention: a prospective cohort study

Abstract: BackgroundWe sought to determine whether maternal Medicaid retention influences child Medicaid retention because caregivers play a critical role in assuring children’s health access.MethodsWe conducted a longitudinal prospective cohort study of a convenience sample of 604 Medicaid-eligible mother-child dyads followed from the infant’s birth through 24 months of age with parent surveys. Individual enrollment status was abstracted from administrative Medicaid eligibility files. Generalized estimating equations q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Similarly, individuals with two consecutive months enrolled in Medicaid after their first observed disenrollment were classified as re-enrolled. Previous research using Medicaid and other insurance data has also relied on a 2-month requirement for disenrollment and re-enrollment (Ji et al, 2017; Pati et al, 2018; Tao & Patel, 2016; Zhang et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, individuals with two consecutive months enrolled in Medicaid after their first observed disenrollment were classified as re-enrolled. Previous research using Medicaid and other insurance data has also relied on a 2-month requirement for disenrollment and re-enrollment (Ji et al, 2017; Pati et al, 2018; Tao & Patel, 2016; Zhang et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Children are more likely to stay enrolled in Medicaid if they have low household incomes or poor health status, or if their parents are also enrolled in Medicaid. [29][30][31] In our study population we observed differential loss to follow-up by race, length of maternal Medicaid enrollment, and health status (see appendix exhibit A2). 27 To reduce the bias in our estimates due to this differential loss to follow-up, we constructed inverse-probability-of-censoring weights.…”
Section: Discussionmentioning
confidence: 83%
“…Because HIV disproportionately affects racial, ethnic and sexual minority communities and people living in poverty, barriers to insurance coverage may affect not only YPHIV and YAPHIV, but also youth and young adults perinatally exposed to HIV but uninfected (YPHEU and YAPHEU), also born to women living with HIV (WLHIV). 21,22 Studies have shown increased burden of mental health challenges among both children and adolescents living with perinatally-acquired HIV (PHIV) and those who were perinatally exposed to HIV but uninfected compared with the general US youth population, with some evidence for greater burden among YPHEU. 23,24 Studies have also highlighted that adverse health outcomes may be attributed to sociocontextual factors such as education, access to care, and social support among those perinatally exposed to HIV, but uninfected compared with those unexposed.…”
Section: Introductionmentioning
confidence: 99%
“…Because HIV disproportionately affects racial, ethnic and sexual minority communities and people living in poverty, barriers to insurance coverage may affect not only YPHIV and YAPHIV, but also youth and young adults perinatally exposed to HIV but uninfected (YPHEU and YAPHEU), also born to women living with HIV (WLHIV). 21,22…”
Section: Introductionmentioning
confidence: 99%